Characterization of Firebrands Released From Different Burning Tree Species - Almeida, Miguel; Porto, Leonardo; Viegas, Domingos (Frontiers in Mechanical Engineering, 2021)
The number, dimensions and initial velocity of the firebrands released from burning Quercus suber, Eucalyptus globulus, Quercus robur and Pinus pinaster trees were analyzed in laboratory experiments using a particle image velocimetry system. Additionally, the flame height, tree mass decay, vertical flow velocity and temperature at the top of the trees were measured during the experiments. The relationship between the various parameters was analyzed and a good rapport connection between the flame height and the number and total estimated volume of the firebrands was found. The specimens burnt were mostly young trees, so. Therefore, large particles like (e.g., pine cones, or thick pieces of trunk barks, and branches) were not included in this study because they were not present. considered in the analysis. Actually, the firebrands produced in the laboratory tests, mainly burning leaves, had less than 1600mm2 of cross-sectional area, having potential to cause short distance spotting (up to tens of meters). Quercus suber and Quercus robur trees were the species that produced more firebrands, both in terms of number and of total volume. On the other hand, Eucalyptus globulus was the species that showed the lowest production of firebrands. Experiments with Eucalyptus globulus and Quercus suber trees were those resulting in larger values of temperature and vertical airflow velocity during the burning process. Quercus trees are often considered to have a lower fire risk than eucalyptus or pine trees. However, in this study Quercus suber and Quercus robur were the species that produced more firebrands, both in terms of number and of total volume. The tests with Quercus suber were the only ones using specimens from an adult tree, confirming the great importance of the age of trees in the propensity to release firebrands. The results obtained with Quercus robur confirmed the high tendency of this species to originate spot fires at short distance. Thus, these results are of great relevance to afforestation plans and to evaluate the risk of the presence of these species in wildland-urban interface areas.